Colchicine efficacy comparison at varying time points in the peri-operative period for coronary artery disease: a systematic review and meta-analysis of randomized controlled trials - Wei, Zhi-Yang; Lai, Jun-Yu; Li, Ya-Ting; Yu, Xiao-Yan; Liu, Yan-Hong; Hu, Jing-Xuan; Gao, Bei-Bei; Wu, Jian-Guang (Frontiers in Cardiovascular Medicine, 2023)
Over the years, it's found that colchicine offers substantial benefits in secondary prevention in patients with coronary artery disease (CAD). We studied the effects of colchicine timing because there are no guidelines about when to provide it during the perioperative period for patients with CAD.Methods: Up to January 1, 2023, seven electronic literature databases were (screened including three English databases and four Chinese databases), randomized controlled trial included only treatment with colchicine in the perioperative period of CAD. The Cochrane Evaluation Tool was used to judge the risk of bias in research.Statistical analysis was performed by Stata 16.0 software.We evaluated twelve studies that found colchicine to be effective in decreasing the occurrence of major adverse cardiac events (MACEs) (p<0.00001), but it also raised the rate of adverse events (p=0.001). Subgroup analysis showed the same benefit in lowering the incidence of MACE with continuous administration of a total daily dose of 0.5 mg postoperatively while minimizing drug-related side effects in the patients(p=0.03); When it comes to preventing surgical stroke occurrences, postoperative administration is more effective(p=0.006); While the effect of simultaneous preoperative and postoperative administration was marginally greater than other periods in reducing postoperative hs-CRP levels(p=0.02).Colchicine, a traditional anti-inflammatory drug, also reduces the risk of MACE by reducing inflammation after PCI. Administration at different periods had no significant effect on decreasing the occurrence of MACE, but when administered postoperatively, we advise continuous administration with a total daily dose of 0.5 mg to obtain the same benefit while minimizing the drug's side effects; Postoperative administration is the better measure to prevent postoperative stroke events; Due to the effective anti-inflammatory effect of colchicine, we recommend its use as early as possible in the perioperative period and it's continued using at low doses in the postoperative period.